Engineering as a global profession technical and ethical standards - Davis, Michael, 1943- (Rowman & Littlefield, 2021)
"While this book begins with the analysis of engineering as a profession, it concentrates on a question that the last two decades seem to have made critical: Is engineering one global profession (like medicine) or many national or regional professions (like law)? While science and technology studies (STS) have increasingly taken an "empirical turn", much of STS research is unclear enough about the professional responsibility of engineers that STS still tends to avoid the subject, leaving engineering ethics without the empirical research needed to teach it as a global profession. The philosophy of technology has tended to do the same. This book's intervention is to improve the way STS, as well as the philosophy of technology, approaches the study of engineering. This is work in the philosophy of engineering and the attempt to understand engineering as a reasonable undertaking"--